The troublemaker's teaparty : a manual for effective citizen action - Dobson, Charles (New Society Publishers, 2003)
"The Troublemaker's Teaparty is a complete how-to for people who want to make a difference beyond their personal lives. It is written for individuals and small groups with few resources, unlike similar books that are intended for nonprofits with staff and funding. The book will help those trying to improve their communities, as well as those trying to address issues that transcend place such as health care, globalization, and environmental protection."--Jacket.